Dynamics of a contact continuum Singaporean English - Ho, Mian-Lian; Platt, John Talbot (Clarendon Press, 1993)
Singaporean English is an indigenized variety of the language which has developed chiefly through English-medium education. The authors of this book investigate the various factors influencing the indigenization of the language and its use in the family and the wider community. They present the results of quantitative research based on recordings of spontaneous speech of ethnically Chinese Singaporeans who have received an English-medium education. They also trace the influence on Singaporean English of Chinese, Malay, and Indian language characteristics, and examine certain linguistic features in detail, such as the formation of plurals, the use of the past tense, and the verb be. This study will be invaluable for linguistic researchers; it also has important pedagogical implications for curriculum planners and language teachers.
Keywords: Engels; Englisch; Gesellschaft; English language -- Social aspects -- Singapore; Languages in contact -- Singapore; Singapur